Trends and associations of Trichomonas vaginalis infection in men and women with genital discharge syndromes in Johannesburg, South Africa. Issue 6 (20th April 2013) - Lewis, David A; Marsh, Kimberly; Radebe, Frans; Maseko, Venessa; Hughes, Gwenda
Abstract : Objectives: To better understand the epidemiology of Trichomonas vaginalis infection, we investigated the association between T vaginalis and demographic, clinical, microbiological and behavioural characteristics of patients presenting with genital discharges to a primary healthcare clinic in Johannesburg, South Africa. Methods: During six annual surveys (2007–2012), 1218 cases of male urethral discharge syndrome and 1232 cases of vaginal discharge syndrome were consecutively recruited. Diagnostic methods included nucleic acid amplification ( Neisseria gonorrhoeae, Chlamydia trachomatis, T vaginalis and Mycoplasma genitalium), microscopy (bacterial vaginosis and Candida ) and serology ( Treponema pallidum, herpes simplex virus type 2 (HSV-2) and HIV). Logistic regression analyses and χ 2 tests were used to identify predictors of T vaginalis infection. Results: The prevalence of T vaginalis decreased from 2007 to 2012 (men from 13.4% to 4.8%; women from 33.8 to 23.1%). Overall, 74 (6.1%) men and 291 (23.6%) women were T vaginalis positive, with the highest prevalence in those aged ≥40 years (men 13.6%; women 30.9%). T vaginalis infection occurred more often in pregnant women (adjusted OR (aOR) 2.67; 95% CI 1.29 to 5.54) and in women with serological evidence of T pallidum (aOR 1.63; 95% CI 1.08 to 2.45) or HSV-2 infections (aOR 1.75; 95% CI 1.16 to 2.64). T vaginalis infection occurred less often in men with coexistent gonorrhoea (aOR 0.35; 95% CI 0.21 to 0.57) and in women with either bacterial vaginosis (aOR 0.60; 95% CI 0.44 to 0.82) or Candida morphotypes (OR 0.61; 95% CI 0.43 to 0.86). Conclusions: Although the prevalence of T vaginalis infection has decreased over time, it remains an important cause of genital discharge in South Africa, particularly in older patients and pregnant women.